2018
DOI: 10.1038/s41467-017-02447-7
|View full text |Cite|
|
Sign up to set email alerts
|

Role of outer surface probes for regulating ion gating of nanochannels

Abstract: Nanochannels with functional elements have shown promise for DNA sequencing, single-molecule sensing, and ion gating. Ionic current measurement is currently a benchmark, but is focused solely on the contribution from nanochannels’ inner-wall functional elements (NIWFE); the attributes of functional elements at nanochannels’ outer surface (NOSFE) are nearly ignored, and remain elusive. Here we show that the role of NOSFE and NIWFE for ion gating can be distinguished by constructing DNA architectures using dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 51 publications
1
91
0
3
Order By: Relevance
“…In a very recent work, we made a preliminary experimental to distinguish the contribution of FE IW and FE OS to ionic gating 45 . The FE OS were proved to synergistically enhance the ionic gating efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent work, we made a preliminary experimental to distinguish the contribution of FE IW and FE OS to ionic gating 45 . The FE OS were proved to synergistically enhance the ionic gating efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Although the subunits located at the extracellular entrances of the natural channel proteins play the same important function as those at the inner,5 less attention has been paid to the functionalization on the exterior surfaces of biomimetic nanochannels and the influence of exterior surfaces on the transmembrane ionic transport. Recently, Li et al have demonstrated that the introduction of the functional elements at the outer surface of nanochannels contributed to an enhancement of the ion gating behavior owing to a synergistic effect in alliance with the inner‐wall functional elements 6. However, related experimental researches concerning ion rectification still remain unexplored as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation could be overcome by functionalizing the inner surface of nanopore, e.g., salinization to form a hydrophobic surface 27 . The previous study reports that the synergistically enhanced ion-gating effect induced by the outer and inner surface probe of the nanopore 34 . Therefore, the modification of nanopore will further help us to reversibly modulate the AIE emissions with the multi-stimulus, which is in response to the environmental variations of pH, temperature, force, and photon etc.…”
Section: Discussionmentioning
confidence: 98%